A study of clinical profile and outcome of SAM children admitted in nutritional rehabilitation centre, Patna Medical College and Hospital, Patna, Bihar, India - Tiwari, Anil Kumar; Jaiswal, Anil Kumar; Saurabh, Kumar; ., Priyanka; ., Supriya (International Journal of Contemporary Pediatrics, 2018)
Background: Severe Acute malnutrition (SAM) with severe wasting remains a major killer of children. In Bihar 48% of children are stunted, 21 % are wasted and 7% are severely wasted. Even during the first six months of life, 31% are wasted. Under nutrition generally decreases with the increasing mother’s schooling, better nutritional status of the mother. Stunting and under nutrition are higher in rural areas than in urban areas. Methods: It is a hospital based observational study done between June 2017 to December 2017. A total of 55 SAM patients with medical complications in the age group of 6 months to 60 months admitted in Nutritional Rehabilitation center (NRC), Department of Pediatrics, Patna Medical College, Patna were included in the study. Socio-Economic profile, effectiveness of NRC in treating SAM children, and effect of timely initiation of complementary feed on nutritional status of children were assessed. Results: A total of 55 children were admitted in the NRC of PMCH, Patna during the period of June 2017 to Dec 2017. 56.4% were males and 43.6% were females. 36% o were in the age group of 12months to 24months. 78% belonged to below poverty line. Major medical complications were anemia (53%), LRTI (33%) and acute gastroenteritis (29%). Immunisation was complete in only 45%. In only 53% babies Complimentary feeding was initiated after 6 months of age. 67% of the mothers of SAM children were illiterate. 95% children were discharged after gaining proper weight. Defaulter rate was 4% and death rate was 2%. 78% of the admitted children showed good weight gain i.e.>10 gm/kg/day, whereas in 15% children weight gain was in the range of 5-10 gm/kg/day. Conclusions: Many factors such as literacy, income, age of marriage and sanitation facility indirectly or directly influence the nutritional status of children. NRCs provide life-saving care for children with SAM as demonstrated by the high recovery rate (95%).